The incidence and clinical characteristics of fragile X syndrome in China - Mei, Lianni; Hu, Chunchun; Li, Dongyun; Wang, Ya; Li, Huiping; Zhang, Kaifeng; Zhou, Bingrui; Zhu, Ruoping; Hagerman, Randi J.; Xu, Xiu; Xu, Qiong (Frontiers in Pediatrics, 2023)
Introduction Fragile X syndrome (FXS) is a X-linked neurodevelopmental disorder (NDD). This study aims to investigate the incidence of FXS in Chinese children and analyze the comprehensive clinical characteristics of these FXS children. Methods Children diagnosed with idiopathic NDD were recruited between 2016 and 2021 from the department of Child Health Care, Children's Hospital of Fudan University. We combined tetraplet-primed PCR-capillary electrophoresis and whole exome sequencing (WES)/panel or array-based comparative genomic hybridization (array-CGH) to identify the size of the CGG repeats and the mutations or copy number variations (CNVs) in the genome and in FMR1. The clinical features of FXS children were analyzed according to pediatricians' recording, parental questionnaires, the results of examinations and follow-up. Results The incidence of FXS in Chinese children with idiopathic NDD was 2.4% (42/1753) and in those with FXS, 2.38% had a deletion (1/42). Here, we present the clinical characteristics of 36 children with FXS. Overweight was observed in two boys. The average intelligence quotient (IQ)/development quotient (DQ) of all FXS patients was 48. The average ages of meaningful words and walking alone were 2 years and 10 months and 1 year and 7 months, respectively. The most frequent repetitive behavior was stimulated by hyperarousal to sensory stimulation. On social aspects, social withdrawal, social anxiety, and shyness accounted for 75%, 58%, and 56% of the total number of children, respectively. Approximately 60% of FXS children in this cohort were emotionally labile and prone to temper tantrums. Self-injury and aggression toward others could also be observed, at 19% and 28%, respectively. The most frequent behavioral problem was attention-deficit hyperactivity disorder (ADHD) seen in 64% and the most common facial features were a narrow and elongated face and large or prominent ears in 92% of patients. Discussion Screening of FMR1 full mutation provides the possibility for patients' further medical supports and the clinical features of FXS children obtained in this study will increase the understanding and diagnosis of FXS.